Italian Emigration Law and the Great War: The Fine Line between Protection and Discipline (Italian Review of Legal History, 2020)
The essay investigates the developments of Italian emigration regulation from the first “social legislation” enacted in January 1901 to the post-war consolidated text on emigration, the law decree n. 2205/1919.The aim of this work is to verify whether, and to what extent, the liberal principles on which the 1901 discipline was based were maintained in the face of the progressive growth of state intervention to protect emigration. The hypothesis is that the links existing between the activity of protection of emigrants and the possibility of controlling and governing migratory flows, have emerged in an increasingly evident way with the intensification of the protective action of the State and, also thanks to the upheavals political and institutional issues caused by the Great War, have progressively distorted the original characteristics of the 1901 legislation.
Keywords: freedom of emigration; war; continental emigration; European emigration; the control of migration flows.